A study on the perceived role of local AM Radio Stations during the Typhoon Frank in Pavia, Iloilo - Jagorin, Kim Carlm C.; Sorrosa, Keempee E. (2008.)
The study sought to determine the perception of the respondents towards the role of local AM radio stations during the typhoon Frank. One hundred and twenty respondents were selected from 8 barangays in Pavia, Iloilo namely: Purok I, Pagsanga-an, Ungka I, Mali-ao, Purok IV, Balabag, Amparo and Pandac. Questionnaires were used to obtain data of the study. Results showed that the respondents perceived radio as an information disseminator during the typhoon Frank and according to the result of the survey the news aired during teh typhoon Frank were mostly about information and updates about the typhoon. They also claimed that Aksyon Radyo was the most accessible, most listened to, most responsive and most helpful during the time of typhoon Frank. This claim was supported by the result of the survey.
Thesis (Undergraduate, Bachelor of Arts in Broadcast Communication) University of the Philippines Visayas, Miagao, Iloilo.
Keywords: AM Radio Stations; Typhoon -- Frank; Perceptions -- AM Radio Stations